The Relationship between Food Myths and the Incidence of Anaemia among Pregnant Women in the Third Trimester of Pregnancy - Izzati, Aghnia Ilma; Tamtomo, Didik Gunawan; Rahardjo, Setyo Sri (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Nutrition in pregnant women is an important factor affecting maternal and fetal health. Anaemia is one of the problems in pregnancy. Lack of protein and iron intake is one of the factors causing anaemia. Cultural beliefs and knowledge such as food myths and taboos can give bad impacts on maternal and child health. Objective: To determine the relationship between food myths and the incidence of anaemia among pregnant women in the third trimester of pregnancy. Materials and Methods: This observational research used a cross-sectional design. The determination of the subject used a simple random sampling and the obtained samples were Puskesmas Margasari, Puskesmas Kesambi, and Puskesmas Lebaksiu. The population was pregnant women in the third trimester of pregnancy in Tegal District with the subject of 120 pregnant women. The data were collected using a food myth questionnaire. Data were analysed using Chi-Square. Result: There was a relationship between belief in food myths and the incidence of anaemia among pregnant women in the third trimester of pregnancy in Tegal District (p-value: 0.002). International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 200-203